Dielectric and ferroelectric behavior in 8/40/60 PLZT ceramics - Ladapak Chumprasert (2018)
This paper describes the relationship between sintering time conditons, tetragonality from phase formation, dielectric and ferroelectric characteristics of tetragonal PLZT (lanthanum modified lead zirconate titanate) ceramics with the pressureless sintering conditions. Ferroelectric compounds of Pb0.92La0.08(Zr0.4,Ti0.6)0.98)O3, PLZT 8/40/60, were prepared using mixed-oxide synthetic route via a rapid vibro-milling method. X-ray diffraction, is used to observe the tetragonality characteristic and the presence of pyrochlore. When sintering time was increased (≥ 8 hours), pyrochlore was developed. It can be observed that with the increased sintering time, it were changed the structure and ferroelectric behavior of the PLZT ceramics. © (2014) Trans Tech Publications, Switzerland.